Who Was Concerned about Radiation, Food Safety, and Natural Disasters after the Great East Japan Earthquake and Fukushima Catastrophe? A Nationwide Cross-Sectional Survey in 2012 - Sugimoto, Takashi (Public Library of Science, 2014)
BACKGROUND: Disaster-related concerns by sub-populations have not been clarified after the great East Japan earthquake and the Fukushima nuclear power plant incidents. This paper assesses who was concerned about radiation, food safety, and natural disasters among the general population in order to buffer such concerns effectively. METHODS: The hypothesis that women, parents, and family caregivers were most concerned about radiation, food safety, and natural disaster was tested using a varying-intercept multivariable logistic regression with 5809 responses from a nationwide cross-sectional survey random-sampled in March 2012. RESULTS: Many people were at least occasionally concerned about radiation (53.5%), food safety (47.3%), and about natural disaster (69.5%). Women were more concerned than men about radiation (OR = 1.67; 95% CI = 1.35–2.06), food safety (1.70; 1.38–2.10), and natural disasters (1.74; 1.39–2.19). Parents and family care needs were not significant. Married couples were more concerned about radiation (1.53; 1.33–1.77), food safety (1.38; 1.20–1.59), and natural disasters (1.30; 1.12–1.52). Age, child-cohabitation, college-completion, retirement status, homemaker status, and the house-damage certificate of the last disaster were also associated with at least one concern. Participants from the Kanto region were more concerned about radiation (2.08; 1.58–2.74) and food safety (1.30; 1.07–1.59), which demonstrate similar positive associations to participants from Tohoku where a disaster relief act was invoked (3.36; 2.25–5.01 about radiation, 1.49; 1.08–2.06 about food safety). CONCLUSIONS: Sectioning the populations by gender and other demographics will clarify prospective targets for interventions, allow for a better understanding of post-disaster concerns, and help communicate relevant information effectively.